2016
DOI: 10.7863/ultra.15.05037
|View full text |Cite
|
Sign up to set email alerts
|

B‐Mode Sonographic Assessment of the Posterior Circumflex Humeral Artery

Abstract: Elite overhead athletes are at risk of vascular injury due to repetitive abduction and external rotation of the dominant arm. The posterior circumflex humeral artery (PCHA) is prone to degeneration, aneurysm formation, and thrombosis in elite volleyball players and baseball pitchers. The prevalence of PCHA-related thromboembolic complications is unknown in this population. However, the prevalence of symptoms associated with digital ischemia is 31% in elite volleyball players. A standardized noninvasive imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Both MRA and CTA were used to make the final diagnosis in these two pitchers. van de Pol et al 7 recently developed the SPI-US study, a protocol for quickly, accurately, and cost effectively evaluating the PHCA with ultrasonography in a 5- to 10-minute examination. Their work has been shown to be both reliable and reproducible, and although both athletes in this report had diagnoses made after MRA and/or CTA, it is logical that an appropriate ultrasonography protocol could have resulted in a similar diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both MRA and CTA were used to make the final diagnosis in these two pitchers. van de Pol et al 7 recently developed the SPI-US study, a protocol for quickly, accurately, and cost effectively evaluating the PHCA with ultrasonography in a 5- to 10-minute examination. Their work has been shown to be both reliable and reproducible, and although both athletes in this report had diagnoses made after MRA and/or CTA, it is logical that an appropriate ultrasonography protocol could have resulted in a similar diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of data published from 1972 to 2015 revealed only 60 athletes with axillary artery and/or branch occlusions or aneurysms. 1 2 3 4 5 6 7 8 9 10 Of these 60, approximately 75% were baseball pitchers, with the remaining 25% participating in volleyball, windsurfing, handball, kayaking, tennis, and softball. We present the cases of two collegiate baseball pitchers who developed PHCA aneurysms to increase awareness of this relatively uncommon injury in light of new diagnostic protocols and increased prevalence.…”
mentioning
confidence: 99%
“…Volleyball players with confirmed digital ischemia present themselves late in disease with severely disabling coldness, discolouration, pain and paraesthesia in the dominant hand (Van de Pol et al, 2016). Active surveillance enables identification of apparently innocuous symptoms, like coldness and discolouration, at an early stage, and might prevent thromboembolic complications, irreversible tissue damage and possibly surgical ligation of the PCHA (Van de Pol et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were: (1) being an elite male indoor volleyball player active in the Dutch national top or second league in the seasons 2013-2014; and (2) written informed consent. To secure sufficient variety in players with and without symptoms of digital ischemia, 84 volleyball players who reported at least one symptom of cold, blue or pale digits in the dominant hand during or directly after practice or competition were selected from a previous study, and supplemented with volleyball players who reported no symptoms (n = 22) (Van de Pol et al, 2016).…”
Section: Participant Selectionmentioning
confidence: 99%